PERCEPTION OF SUPERMARKET OWNERS ON THE IMPLEMENTATION OF LAW N°5414/15 - Guillermo Dávalos Giménez, Fabio; Leticia Gamarra, Maria; Soledad Gómez Centurión, Gabriela (Revista Gênero e Interdisciplinaridade, 2023)
Currently, the country’s businesses are implementing Law 5414/15 for the Promotion of Reduction in the use of polyethylene plastic bags. Supermarket owners are affected by this new reality, given that they are the main distributors of single-use plastic bags for packaging and transporting merchandise. The main objective of this research was to find out the perception of supermarket owners regarding the implementation of said law. Within the framework of this research, the survey was applied as a data collection instrument, through a questionnaire with closed questions, addressed to a population of 10 supermarkets located in the main busiest neighborhoods of Ciudad del Este. This research was developed under the model of the quantitative approach and the descriptive level. With the results of the data collection instrument, it was possible to observe an acceptance by the businessmen since it implies savings in terms of inputs within their installation for the comfort of clients. In addition, it is necessary to implement strategies and awareness campaigns for the final consumer for the correct use of plastic bags in such a way that they can be reused and that their impact on the environment is minimal.